Analysis of the Impact of Retail Marketing Mix on Purchasing Decisions through Customer Satisfaction - Kulsum, Siti Umi; Setiawan , Rahyuniati; Herlianti , Anggun Oktavia (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the influence of Retail Marketing Mix on Purchasing Decisions through Customer Satisfaction on Berkah Family Retail consumers located in Andir Market. Berkah Family Retail has a strategic role in supporting economic resilience and regional development, so increasing customer satisfaction is a very important aspect. Based on the context, customer satisfaction is seen as one of the main strategic advantages, while Purchasing Decisions are understood as a series of cognitive processes and consumer behavior in considering, choosing, and finally deciding to buy a product or service. The research method uses a quantitative approach with a random sampling technique, involving 107 respondents who are active customers of Berkah Family Retail. The data collection technique was carried out through distributing questionnaires, then analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software version 4.0. The results of the study indicate that Retail Marketing Mix has a direct and significant effect on Purchasing Decisions, and Purchasing Decisions have a significant effect on Customer Satisfaction, with a t-statistic of 6.199 and a p-value of 0.000, which indicates the hypothesis is accepted. Therefore, this research provides theoretical contributions to the development of retail marketing science and practical implications for small business management, particularly in efforts to improve customer experience and satisfaction.